Indigenous Australian texts in European English departments - Polak, Iva (ELOPE (Ljubljana), 2013)
Though non-canonical Anglophone courses in the curriculum of European English departments are no longer seen as oddity, they are often regarded as "marginal" in comparison to the British and American canon. However, courses focusing on the cultural output of postcolonial voices, moreover of the most marginal of postcolonial voices, do not only challenge the extent to which we have managed to shift from Eurocentrism in literary theory, but also reveal the complexities of the current cultural trends, such as the frequently evoked policy of multiculturalism. The paper argues that courses which include texts by Indigenous Australian authors reveal the story of survival in a country that is literally multicultural, and stress the importance of one's own place of utterance, which is as local as it is global. The above issues are exemplified by the works of the famous Aboriginal writers Doris Pilkington/Nugi Garimara (Follow the Rabbit-Proof Fence, 1996), John Muk Muk Burke (Bridge of Triangles, 1994) and Alexis Wright (Carpentaria, 2006).
Keywords: anglofonske alternative; avstralska besedila domorodcev; Europe; Evropa; globalno in lokalno; multikulturnost; poučevanje književnosti